A Concept for Wireless Network Integration in Production System Planning - Vukovic, Petar; Lechler, Tobias; Franke, Jörg (IEEE International Conference on Emerging Technologies and Factory Automation, ETFA, 2020)
In the context of Industry 4.0, the flexibility of production systems rises constantly. To fulfil this demand, wireless instead of classic wired communication networks can be used. This trend is supported by the advancement of new network standards such as 5G. Current design of wireless networks in production systems in the early planning phase relies on best practices and experience. In following planning phases worst case calculations are used to verify the network topology. Taking the dynamic behaviour of flexible production systems into account, networks are constantly changing. In this paper, existing discrete event simulation of production systems is augmented with planning components of wireless networks to allow a more precise planning of production systems using wireless communication.
CRIS-Team Scopus Importer:2020-10-30
Keywords: 5G; discrete event simulation; production system planning; wireless networks

Kommunikationsbedürfnisse flexibler Produktionsanlagen - Vukovic, Petar; Franke, Jörg (VDI Berichte, 2020)
Industrial communication technology often causes difficulties during planning and operation. For this reason, many planners still rely on wired communication technology because it is easier to plan and less susceptible to failures. The trend towards digitalization and Industry 4.0 can only be successfully implemented by making production more flexible. A pervasive flexi-bilisation can only be achieved by incorporating radio-based communication technologies and is therefore becoming more and more popular. Due to a lack of know-how in radio technologies, simulations can provide optimum support in planning. The earlier these simulations are used, the lower the error costs are due to timely correction. Since the manufacturer and type of communication components are not defined at such an early stage of planning, the communication requirements of applications and devices must be used to make an optimal approximation to the later real communication. This paper presents a type of co-simulation that suggests an optimal positioning of access points based on communication needs. Furthermore, the communication needs and their characteristics are presented.
CRIS-Team Scopus Importer:2023-03-07

Simulation software design as a potential solution to the increasing complexity of industrial communication networks - Vukovic, Petar; Collischon, Matthias; Franke, Jörg (Procedia CIRP, 2020)
This paper presents results from a survey of industrial communication network administrators concerning their experience with these networks, complications in their operation as well as the utilization of simulation software. Our results show that most respondents consider these networks relatively complex and expect the complexity to increase in the future. Simulation software is seen as a potential counter to this complexity, but they are rarely used. Thus, we further provide a short introduction to simulation software for industrial communication networks.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Industrial communication; Industry 4.0; Network simulation; Survey